The Portrayal of Womanhood in I am Woman Song Lyrics by Emmy Meli - Meriska Yosiana; Chintia Handayani (Asosiasi Dosen Muda Indonesia, 2025)
This study examines the portrayal of womanhood in the song I Am Woman by Emmy Meli using Simone de Beauvoir’s feminist theory and a linguistic features approach. The research applies a descriptive qualitative method, with the song lyrics as the primary data. Data were collected through documentation and analyzed by identifying linguistic features such as first-person pronouns, declarative sentences, repetition, evaluative adjectives, and clause structures. These features were interpreted through a feminist literary perspective to explore representations of womanhood. The findings reveal that the song portrays womanhood as empowered, autonomous, and self-defined. Women are represented as conscious subjects who assert agency, resist patriarchal limitations, and construct their identities through self-awareness and existential freedom. The study demonstrates that linguistic choices in contemporary song lyrics can function as feminist discourse that challenges traditional gender stereotypes and redefines womanhood as a process of becoming rather than a biologically determined identity.